Supracostal Punctures for Percutaneous Nephrolithotomy: Factors that Predict Safety, Success, and Stone-Free Rate in Patients with Renal Stone (Mugda Medical College Journal, 2026)
Percutaneous nephrolithotomy (PCNL) is the standard treatment for large or complex renal stones. Supracostal puncture offers an alternative access route when infra-costal access is challenging, but it carries potential risks. A cross-sectional, observational study was conducted in the Department of Urology, Mugda Medical College Hospital, Dhaka, Bangladesh, between January 2022 and December 2024, to evaluate the safety, success, and stone-free rates of supracostal PCNL and identify factors predicting outcomes in patients with renal stones. A total of of 70 patients (40 males and 30 females) undergoing PCNL via supracostal puncture were included in this study. Stone characteristics, puncture levels, operative details, complications, and stone-free rates were analyzed. The mean age of the patients was 29.6±8.4 years. Stone-free rate (SFR) was 89.4%. Complications occurred in 14.3% of the patients including intraoperative haemorrhage (5.7%), hydrothorax (4.3 pneumothorax (2.9%), and delayed haemorrhage (1.4%). Multivariate logistic regression analysis showed that stone size (OR=0.65, 95% CI 0.48–0.89, p